(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sukuryadi, Harahab N, Primyastanto M, Hadi AP. 2021. Short Communication: Structure and composition of mangrove vegetation in Lembar bay area, West Lombok District, Indonesia. Biodiversitas 22: 5585-5592. One of the potential natural resources of coastal areas in West Lombok District, West Nusa Tenggara Province, Indonesia is the 501.9-ha mangrove ecosystem. The purpose of this study was to analyze the structure and composition of mangroves in the Lembar bay area. The study used field observation methods based on predetermined plots. The results showed that the composition of mangroves in the Lembar Bay area consisted of Avicennia alba Bl, Avicennia marina (Forsk) Vierh, Bruguiera cylindrica (L) Bl, Ceriop decandra (Griff) Ding Hou, Ceriop tagal (Perr) C.B. Rob, Lumnitzera littorea (Jack) Voight, Lumnitzera racemosa Willd. Var, Phemphis acidula, Rhizhopora stylosa Griff, Rhizophora apiculata Bl, Rhizophora mucronata Lmk, and Sonneratia alba J.E. Smith. The mangrove vegetation at tree level was composed of 12 species dominated by Rhizhopora stylosa Griff and Rhizophora mucronata Lmk, with Importance Value Index (IVI) of 56.05 and 48.89, respectively, at sapling level 9 species dominated by Rhizhopora stylosa Griff, Bruguiera cylindrica, and Rhizophora mucronata, with IVI of 47.46, 33.33, and 31.07 respectively, and at the seedling level 7 species dominated by Rhizhopora stylosa Griff and Rhizophora mucronata Lmk, with IVI of 47.71 and 37.76, respectively.